Optimizing the Use of Digital Technology in Building a Community Network of Consumption of Small and Medium Enterprises’ Products during the COVID-19 Pandemic: The Case of Depok, Indonesia - Ichmi Yani Arinda Rohmah; Andi Achdian (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2021)
The massive spread of the COVID-19 pandemic which started in the mid-2020 has had a significant impact on the sustainability of the production and marketing activities of goods and services by Small and Medium Enterprises (SMEs). In the context of Indonesia, the so-called policy Large Scale Social Restriction encourages small and medium-sized business groups to find strategic ways so that they can continue to carry out production and marketing activities. One of the strategic ways is building a network of people who consume goods by using digital technology. This study analyses the strategies of small and medium-sized business groups in building a community network of the consumption of small and medium-sized business products through digital technology during the COVID-19 pandemic with special reference to the case of Depok, in Indonesia. This is a descriptive qualitative study with interview, observation, and documentation techniques. The findings show that small and medium enterprises use several digital applications to be able to connect individuals to create a consumption group of “common taste” so that those small and medium-sized enterprises could maintain the continuity of selling their goods or products. As a result, this strategic method is proven to be quite beneficial for small and medium business groups.